Spatiotemporal pattern variations of daily precipitation concentration and their relationship with possible causes in the Yangtze River Delta, China. Issue 3 (25th November 2021) - Mei, Chao; Liu, Jiahong; Huang, Ze; Wang, Hao; Wang, Kaibo; Shao, Weiwei; Li, Meng
Abstract: Understanding the spatiotemporal pattern of precipitation concentration is important in the water cycle under changing environments. In this study, the daily precipitation concentration index in the Yangtze River Delta in China is calculated based on the Lorenz curves obtained from the observed data of 36 meteorological stations from 1960 to 2017, and spatiotemporal pattern variations and their possible causes are investigated. The driving forces of elevation, SUNSPOT, El Niño-Antarctic Oscillation, Pacific Decade Oscillation, and Arctic Oscillation are detected with correlation and wavelet analysis. Results show that, the daily precipitation concentration index ranges from 0.55 to 0.62 during the study period, 22 of 36 stations (accounting for 61%) show increasing trends, while three stations increase significantly at the 95% significant level. Relationship analysis indicates that the daily precipitation concentration shows a slightly negative correlation with elevation, while the relationships with SUNSPOT, El Niño-Antarctic Oscillation, Pacific Decade Oscillation, and Arctic Oscillation are complicated and diverse, there are different correlations and significance levels in different years. Further analysis shows that SUNSPOT is significantly correlated with El Niño-Antarctic Oscillation, Pacific Decade Oscillation, and Arctic Oscillation, which suggests that SUNSPOT may be an important factor that drives the changes of the three large-scale atmosphere circulation factors and causes precipitation concentration changing indirectly. These results provide further understanding of precipitation variations, which is meaningful for regional flood risk management under climate change. HIGHLIGHTS: Spatiotemporal variations of daily precipitation concentration in the Yangtze River Delta are investigated. Daily precipitation concentration shows a strong spatial heterogeneity overall. Large-scale atmospheric circulation and SUNSPOTS are possible driving forces.